درجة توافر أبعاد الرشاقة الاستراتيجية في المديريات العامة للتربية والتعليم بسلطنة عمان - الجرايدة، محمد سليمان مفضي (جامعة البحرين - مركز النشر العلمي, 2021)
هدفت هذه الدراسة تعرف درجة توافر أبعاد الرشاقة الاستراتيجية في المديريات العامة للتربية والتعليم بسلطنة عمان. ومن أجل تحقيق الهدف تم بناء استبانة مكونة من (٦٩) فقرة، موزعة على سبعة مجالات رئيسة، وبعد التحقق من صدقها، وثباتها، تم تطبيقها على (١٩٠) مدير دائرة ومساعديه ورؤساء الأقسام في المديريات العامة للتربية والتعليم في سلطنة عمان في العام الدراسي ٢٠١٩/ ٢٠٢٠، وللإجابة عن أسئلة الدراسة استخدمت المتوسطات الحسابية، والانحرافات المعيارية، واستخدام اختبار T-Test، ومن أبرز النتائج التي توصلت إليها أن درجة توافر أبعاد الرشاقة الاستراتيجية في المديريات العامة للتربية والتعليم بسلطنة عمان متوسطة، كذلك أظهرت نتائج الدراسة أنه لا توجد فروق ذات دلالة إحصائية عند مستوى دلالة (0.05 ≥ α) في استجابات أفراد العينة حول درجة توافر أبعاد الرشاقة الاستراتيجية في المديريات العامة للتربية والتعليم بسلطنة عمان باختلاف متغير النوع الاجتماعي، وسنوات الخبرة، والمؤهل العلمي، ومن أبرز التوصيات ضرورة توافر الفرص المناسبة للتنمية المهنية لجميع العاملين في المديرية، كذلك ضرورة وجود آلية واضحة ومتفق عليها لتصحيح الانحرافات في فيها وضرورة استشعار حاجات المجتمع المحلي ومؤسساته باستمرار.
This study aims at identifying the degree of the requirements for Strategic Agility at the General directorates of the Ministry of Education in the Sultanate of Oman. To achieve the objective of the study, a questionnaire composed of 69 items was designed and distributed seven main fields. After checking the validity and reliability of the questionnaire, 190 district managers and their deputies and heads of divisions were asked to respond to the questionnaire during the academic year 2019-2020. To evaluate the responses, several statistical procedures were used: means, standard deviations, and T test. The study found that the degree of the degree of the requirements for Strategic Agility at the General directorates of the Ministry of Education in the Sultanate of Oman was medium. The results also indicated no significant differences (α< 0.05) due to gender, years of experience, academic qualifications. In the light of the findings, the researcher recommend he necessity of providing appropriate opportunities for professional development for all workers in the Directorate, as well as the necessity of having a clear and agreed mechanism to correct deviations in it and the need to continuously feel the needs of the local community and its institutions.
Keywords: المؤسسات التعليمية -- الإدارة التعليمية -- الرشاقة الاستراتيجية -- المديريات العامة للتربية والتعليم -- سلطنة عمان